Design, fabrication and performance evaluation of a domestic dish washing machine (2012)
Plate washing is a daily activity across the globe which involves a lot of energy to accomplish manually or mechanically. The objective of this work is to design and fabricate a dish washing machine that is efficient and easy to operate. Stainless steel and mild steel was used for the construction of the machine considering their availability, cost reduction and corrosion resistance. The motor used a power of 0.75hp (559.5 W), voltage of 240V and a speed of rotation of “1200 r.p.m” which was reduced to “100 r.p.m” using a reduction gear of velocity ratio (V.R) “12:1”, the shaft torque being “53.4 N-m”. The plates were washed and rinsed in a separate basin using a liquid detergent and clean water following appropriate measure per cycle. Detailed design drawings of all the machine parts were drawn using AutoCAD. The performance analysis of the machine shows that the number of plates washed and the time taken were 20 plates per minute (1min), 5 plates per minute for the machine and manual operation respectively. The capacity of the machine is 20 plates per minute (1880 per hour). The machine washes plates without breakages.